THE IMPORTANCE OF COMPETENCE TOWARDS THE QUALITY OF EDUCATION SERVICES IN INDONESIA - Wati, Ratna; Suradinata, Ermaya; Maryani, Dedeh; Sigit Pudjianto, Widodo (Dinasti International Journal of Digital Business Management, 2021)
The spread of Covid-19 in Indonesia till now has transformed particularly in education system which was marked by the issuance of the 4 Ministerial Decrees, thus affecting the learning process in educational units throughout Indonesia. Those phenomenon that used as an current object for this research is the quality of education services at State senior high school in West Java Province. This research aims to discuss the impact caused by competence on the quality of educational services. The research sample earned 381 respondents who was taken from a population of 54,150 people through Krejcie sampling technique. Collecting data used literature review and questionnaires with data analysis technique used SEM analysis and descriptive analysis. The results from this research has proven that the amount of the influence fr Competence to the Quality of Education Services at State Senior High Schools in West Java Province reached 0.55, which is quite strong and significant.